Claiming places reading Acts through the lens of ancient colonization - Moore, Eric C., 1976- (Wissenschaftliche Untersuchungen zum Neuen Testament., 2020)
"In this study, Eric C. Moore examines Acts of the Apostles against the backdrop of colonization in the ancient Mediterranean world. He shows how common cultural beliefs concerning the foundation of new communities shape Luke's account as well." --